2018
DOI: 10.3389/fpsyg.2018.01820
|View full text |Cite
|
Sign up to set email alerts
|

Informativeness of Auditory Stimuli Does Not Affect EEG Signal Diversity

Abstract: Brain signal diversity constitutes a robust neuronal marker of the global states of consciousness. It has been demonstrated that, in comparison to the resting wakefulness, signal diversity is lower during unconscious states, and higher during psychedelic states. A plausible interpretation of these findings is that the neuronal diversity corresponds to the diversity of subjective conscious experiences. Therefore, in the present study we varied an information rate processed by the subjects and hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 63 publications
4
8
1
Order By: Relevance
“…In line with this, Mensen and colleagues 33 found that the diversity of EEG-evoked responses was higher when participants saw natural, meaningful images in comparison to artificially generated, meaningless ones. However, in our previous study, in which we used auditory stimuli that varied in terms of information rate and meaningfulness, we found no effect of such manipulation on EEG signal diversity 34 . Relatedly, several studies have compared the diversity of continuous electrophysiological signals recorded during active perception and the resting state: data from three studies indicated that visual perception was related to greater signal diversity than the resting state 21 , 31 , 35 , but three studies investigating auditory perception found it was related to lower diversity in comparison to the resting state 21 , 34 , 35 .…”
Section: Introductioncontrasting
confidence: 56%
“…In line with this, Mensen and colleagues 33 found that the diversity of EEG-evoked responses was higher when participants saw natural, meaningful images in comparison to artificially generated, meaningless ones. However, in our previous study, in which we used auditory stimuli that varied in terms of information rate and meaningfulness, we found no effect of such manipulation on EEG signal diversity 34 . Relatedly, several studies have compared the diversity of continuous electrophysiological signals recorded during active perception and the resting state: data from three studies indicated that visual perception was related to greater signal diversity than the resting state 21 , 31 , 35 , but three studies investigating auditory perception found it was related to lower diversity in comparison to the resting state 21 , 34 , 35 .…”
Section: Introductioncontrasting
confidence: 56%
“…There was no significant correlation between posterior LZC and subjective scores of dream experience diversity and vividness. While some promising results in this direction have been reported earlier, particularly in studies of psychedelics ( Schartner et al, 2017a ; Timmermann et al, 2019 ) and “meaningfulness” of presented stimuli ( Boly et al, 2015 ), LZC has also been found to be unresponsive to the information rate of auditory stimuli ( Bola et al, 2018 ).…”
Section: Discussionmentioning
confidence: 76%
“…It is not yet clear whether signal diversity measures are able to do this. For example, while Timmermann et al (2019) observed that the variation in LZC over time mirrored the self-reported intensity of the ongoing psychedelic experience, Bola et al (2018) found LZC to be unaffected by the presentation rate of audio stimuli (recordings of book excerpts).…”
Section: Introductionmentioning
confidence: 99%
“…This was despite the fact that in all three conditions (movie, TV noise and scrambled movie), each stimulus was equally as differentiated in terms of low-level perceptual content. A similar study conducted in the auditory domain in EEG data, using normal speech at two different speeds and backwards speech, did not find a difference between these conditions ( Bola et al. 2018 ), although the difference in meaningful information content between these two conditions, which was assumed to be higher for the coherent speech than for the incomprehensible backwards speech, may not be sufficient to differentiate them in neural data.…”
Section: Resting-state Neural Complexity and Dimensions Of Consciousnessmentioning
confidence: 86%